Pengembangan Materi Perang Teluk Persia (Iran–Irak) 1980–1988 Dalam Pembelajaran Sejarah Tingkat Lanjut di SMA Negeri 1 Lahat - Lagut Lagut; Supian Supian; Berlian Susetyo; Sarkowi Sarkowi (LP4MK STKIP PGRI Lubuklinggau, 2026)
This study aims to develop advanced-level history learning materials on the Persian Gulf War (Iran–Iraq) 1980–1988 to make them more contextual, analytical, and relevant to the needs of senior high school students. The background of this study is based on the limited development of history learning materials that promote students’ critical and analytical thinking skills in understanding international conflicts. This research was conducted at SMA Negeri 1 Lahat, one of the accredited A public senior high schools in Lahat Regency, South Sumatra, which has adequate learning facilities. The research method used is Research and Development (R&D), which includes stages of needs analysis, material design, development, and limited trials. The research subjects consisted of eleventh-grade students and history teachers. Data collection techniques included observation, interviews, questionnaires, and documentation studies. Data were analyzed using both qualitative and quantitative approaches to assess the feasibility and effectiveness of the developed materials. The results show that the development of Persian Gulf War learning materials based on analytical and contextual approaches can improve students’ understanding of the background, course of the conflict, and its global impacts. In addition, the developed materials are effective in enhancing students’ critical thinking skills, as indicated by improved learning outcomes and positive responses from both students and teachers. Therefore, this development of history learning materials can serve as an innovative alternative in advanced history education at the senior high school level, particularly in studying international conflicts in a more in-depth and meaningful way.